Serum/Plasma Proteomics Methods and Protocols - Simpson, Richard J.; Greening, David W. (Humana Press, 2011)
Blood science has become a cornerstone of multiple disciplines, including clinical chemistry, disease diagnosis, and therapeutic monitoring.  Over the past decade, we have witnessed the advent of increasingly powerful proteomics technologies that allow greater fundamental insights into the blood proteome.  These technological improvements have, in part, fuelled the quest for the discovery of novel blood-based biomarkers of disease. Serum/Plasma Proteomics: Methods and Protocols is a comprehensive resource of protocols for areas, pre-analytical through to analytical, of plasma and serum proteomics. Divided into five convenient sections, this detailed volume covers fractionation strategies for in-depth blood proteome analysis, defined procedures for blood collection, handling and storage, detailed protocols for performing both antibody-based and non-antibody based quantitative assays,  proteome analysis of blood cell compartments, circulating nanomebraneous vesicles and blood-related fluids, and finally data management, statistical design, and bioinformatic challenges. This book, contributed to by leading experts in the field, provides a valuable foundation for the development and application of blood-based proteomics. Written in the highly successful Methods in Molecular Biology™ series format, chapters contain introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and easily accessible, Serum/Plasma Proteomics: Methods and Protocols, with its well-honed methodologies, seeks to serve both professionals and investigators new to the field in an effort to further our knowledge of this fundamental science
Keywords: Life Sciences; Protein Science; Proteomics; Life sciences; Proteins